Concentrations of minerals in pig feed ingredients commonly used in China. Issue 2 (1st April 2017) - Huang, C. F.; Stein, H. H.; Zhang, L. Y.; Li, Defa; Lai, C. H.
Abstract: Mineral concentrations were determined in 13 different feed ingredients commonly used in swine diets. Ingredients included corn and 4 corn co-products: corn gluten feed, corn gluten meal, corn germ meal, and corn distillers dried grains with solubles (DDGS). Wheat, wheat bran, and wheat shorts were also included, and 5 oilseed meals including soybean meal, rapeseed meal, sunflower meal, cottonseed meal, and peanut meal were used as well. Corn grain contained 88.7% dry matter (DM) and 0.46% K (DM basis). Greater concentrations of DM, ash, Ca, P, nonphytate P, Cu, Fe, Mn, and Zn were observed in corn gluten feed, corn DDGS, and corn germ meal compared with corn grain ( P < 0.05). In general, minerals in corn DDGS were approximately three times greater than in corn grain and about 90% of the total P in corn DDGS was in the nonphytate bound form. Corn gluten meal had the least concentrations ( P < 0.05) of most minerals, but the greatest ( P < 0.05) concentrations of Fe (373.55 mg/kg, DM basis), Cu (11.88 mg/kg, DM basis), and Se (0.92 mg/kg, DM basis). On a DM-basis, concentrations of DM, Ca, P, phytate bound P, and Fe in wheat grain were 88.2%, 0.10%, 0.34%, 0.16%, and 53.48 mg/kg, respectively. Wheat bran contained more ( P < 0.05) K, Mg, Cl, Fe, Zn, and Mn compared with wheat and wheat shorts. On a DM-basis, 2.72% K was observed in soybean meal, which was more ( P < 0.05) than in the other oilseed meals. However, rapeseed meal had the greatest ( P < 0.05) concentration of ash (9.37%), Ca (1.01%), P (1.05%), and Fe (526.49 mg/kg) among the oilseed meals, but only 16.2% of the total P in rapeseed meal was non-phytate P. In contrast, more than 50% of the P in soybean meal and peanut meal was non-phytate P. The least ( P < 0.05) concentration of Cu (6.73 mg/kg, DM basis) was observed in rapeseed meal and the greatest ( P < 0.05) concentration (32.75 mg/kg) was analyzed in sunflower meal. Concentrations of most minerals in soybean meal, rapeseed meal, sunflower meal, cottonseed meal, and peanut meal varied considerably compared with published values. In conclusion, the concentration of minerals in 13 commonly used feed ingredients were analyzed and results indicated considerable variation among and within feed ingredients for most minerals, which for some minerals may be a result of differences in minerals in the soil in which the ingredients were grown, but processing likely also contributes to differences among ingredients.